Who’s in charge? Drivers’ Perceived Responsibility in Automated Driving - Erhardsson, Gustav; Lidander, Linnéa (My University, 2020)
The automotive industry is getting closer to releasing vehicles with higher levels of automated driving that can take over driving task completely from the driver. Advanced Driving Assistance Systems (ADAS) are setting new demands on the driver’s interaction with the vehicle. One way to increase the desired behaviour is to ensure that the driver feels appropriately responsible while using the system. This master’s thesis project focuses on two types of automated systems, one where they are responsible for the driving task, and one where they are not. By conducting a secondary analysis of a previous research project conducted by Volvo Cars, this thesis investigated how drivers with little experience in automated systems perceive responsibility in automated vehicles. Several interesting findings were made, and in combination with a review of relevant literature, a conceptual model of responsibility was created. An interview study focused on frequent users of an automated system enabled a narrow focus on perceived responsibility and the connected factors found in the conceptual model. The results from the interview could then be used to validate the conceptual model. Furthermore, two generated concepts investigated how responsibility could be communicated through symbols to the driver and how it could lead them to an appropriate feeling of responsibility. From the study contextual information, individual factors and control were found to affect the drivers feeling of responsibility. Contextual information was found to be derived from the driving environment and the individual factors were found to be trust, experience and expectations of automated driving. Furthermore, different kinds of responsibilities were found to be connected to automated driving, e.g. the responsibility to keep people safe or the responsibility to monitor situations the car is less trusted to handle. A design checklist was created based on the conceptual model to aid the development of automated systems where drivers feel appropriately responsible. The two concepts that were investigated enlighten the complexity of perceived responsibility in automated vehicles, and it could thereby be concluded that a symbol on its own was not enough to communicate responsibility. It was also concluded that the drivers perceived responsibility in automated vehicles must be investigated further to be fully understood.
Keywords: Automated driving, Responsibility, Automotive, Control, Mode confusion